2022
DOI: 10.1136/postgradmedj-2021-141278
|View full text |Cite
|
Sign up to set email alerts
|

Demographics, distribution and experiences of UK clinical academic trainees using GMC NTS Survey data

Abstract: Involvement in research plays an integral role in the delivery of high-quality patient care, benefitting doctors, patients and employers. It is important that access to clinical academic training opportunities are inclusive and equitable. To better understand the academic trainee population, distribution of academic posts and their reported experience of clinical training, we analysed 53 477 anonymous responses from General Medical Council databases and the 2019 National Training Survey. Academic trainees are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…[5] In August 2023, out of a total of 10,446 GP trainees in England 5,379 (51.5%) were from the UK, 594 (5.7%) were from the EU, 4,462 (43%) were from outside of the UK or EU and 11 (0.1%) were from an unknown location. [4] Work by Beckwith et al, [6] found that postgraduate academic trainees are significantly more likely to be White but found no significant difference in the ethnicities of UK graduates in academic posts, as opposed to internationally trained graduates. This suggests that the intersections of country of origin, race and ethnicity may compound inequitable recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In August 2023, out of a total of 10,446 GP trainees in England 5,379 (51.5%) were from the UK, 594 (5.7%) were from the EU, 4,462 (43%) were from outside of the UK or EU and 11 (0.1%) were from an unknown location. [4] Work by Beckwith et al, [6] found that postgraduate academic trainees are significantly more likely to be White but found no significant difference in the ethnicities of UK graduates in academic posts, as opposed to internationally trained graduates. This suggests that the intersections of country of origin, race and ethnicity may compound inequitable recruitment.…”
Section: Introductionmentioning
confidence: 99%